Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/jfpp.13311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of novel nitrite packaging film on the bacterial growth of bison strip-loin steaks

Abstract: This study aimed to determine the effect of different packaging types (overwrapped with polyvinyl chloride film = PVC, vacuum skin packaging = VSP, and vacuum skin packaged with nitrite film = NIT), swabbed steak surface (bottom and top) and ageing time (2 and 9 days) on color stability and spoilage bacteria counts of bison striploin steaks after 7 days of retail display. In comparison to PVC packaging, both VSP and NIT showed more stable color and reduced the bacterial load on the steaks by ∼2log10 for colifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…For example, nitrite-embedded packaging creates a low or anaerobic condition, while PVC is an aerobic packaging. In support, previous research also reported nitrite-embedded packaging had an approximate 1.5-log reduction in psychrophilic bacteria than PVC ( Narváez-Bravo et al, 2017 ).…”
Section: Resultssupporting
confidence: 79%
“…For example, nitrite-embedded packaging creates a low or anaerobic condition, while PVC is an aerobic packaging. In support, previous research also reported nitrite-embedded packaging had an approximate 1.5-log reduction in psychrophilic bacteria than PVC ( Narváez-Bravo et al, 2017 ).…”
Section: Resultssupporting
confidence: 79%
“…High pH and normal pH beef [172] Lamb slices [173] Beef steaks [174] Beef fillets [186] Lamb steaks [187] Beef and pork steaks [188] Bison tenderloin steaks [189] Vacuum packaging inhibits lipid oxidation, thus preventing unpleasant odors and flavors. Packaged in a modified atmosphere with semi-permeable internal vacuum film leads to an attractive bright red color.…”
Section: Treatment Meat Product Effectsmentioning
confidence: 99%
“…www.meatandmusclebiology.com longer duration than tested here (Narváez-Bravo et al, 2017). Evaluations of this packaging system for beef have shown the color remains stable 9 d after packaging (Claus and Du, 2013).…”
Section: Effect Of Nit On Retail Characteristics For Steaks and Burgementioning
confidence: 99%